UPAYA MEDIASI DALAM PENYELESAIAN SENGKETA DI LEMBAGA PERBANKAN - Suherman Suherman (Departemen Hukum Perdata, 2018)
In some countries, mediation was voluntarily dispute settlement. In banking dispute settlement, the dispute arose from customer’s claim over banking services. If the claim unsatisfactory settled, it may lead to banking dispute. The dispute characterized as contractual dispute between the bank and the customer as debtor. At ﬁ rst stage, the customer may request for clariﬁ cation towards the bank. Subsequently, the customer may submit request for mediation to the mediation institution. If the parties (the bank and the customer) reach an agreement on the dispute, the agreement should be written. This article also discuss the advantages and disadvantages of mediation for banking dispute settlement.